Production Of Novel Recombinant Anti-PFHRP2 VNAR-G1 Protein Using Escherichia COLI BL21(DE3) Expression System - Kok, Boon Hui (Pusat Pengajian Teknologi Industri, 2020)
Malaria rapid diagnostic tests (RDTs) act as important antibody-based immunoassays for prompt malaria diagnosis. Conventional monoclonal antibodies (mAbs) are widely used in RDTs but it can be easily degraded at high ambient temperatures. Hence, the shark VNARS might be good alternatives to mAbs due to its higher thermal stability and binding affinity with antigens. In this study, the recombinant antiPfHRP2 VNAR-G1 protein was produced in E. coli expression system through various steps such as recombinant cell isolation, PCR, agarose gel electrophoresis, plasmid extraction, transformation and protein expression.